Nonpolar Inactivation of the Hypervariable Streptococcal Inhibitor of Complement Gene (sic) in Serotype M1 Streptococcus pyogenes Significantly Decreases Mouse Mucosal Colonization - Lukomski, Slawomir (American Society for Microbiology, 2000)
Group A Streptococcus (GAS) is a human pathogen that commonly infects the upper respiratory tract. GAS serotype M1 strains are frequently isolated from human infections and contain the gene encoding the hypervariable streptococcal inhibitor of complement protein (Sic). It was recently shown that Sic variants were rapidly selected on mucosal surfaces in epidemic waves caused by M1 strains, an observation suggesting that Sic participates in host-pathogen interactions on the mucosal surface (N. P. Hoe, K. Nakashima, S. Lukomski, D. Grigsby, M. Liu, P. Kordari, S.-J. Dou, X. Pan, J. Vuopio-Varkila, S. Salmelinna, A. McGeer, D. E. Low, B. Schwartz, A. Schuchat, S. Naidich, D. De Lorenzo, Y.-X. Fu, and J. M. Musser, Nat. Med. 5:924–929, 1999). To test this idea, a new nonpolar mutagenesis method employing a spectinomycin resistance cassette was used to inactivate the sic gene in an M1 GAS strain. The isogenic Sic-negative mutant strain was significantly (P < 0.019) impaired in ability to colonize the mouse mucosal surface after intranasal infection. These results support the hypothesis that the predominance of M1 strains in human infections is related, in part, to a Sic-mediated enhanced colonization ability.